Analisis Efesiensi Energi Berbasis Konsumsi Daya Pada Tiga Generasi Teknologi Lampu - Rikky Yaldi Girsang; Zuraidah Tharo; Muhammad Erpandi Dalimunthe (Jurnal Nasional Teknologi Komputer, 2025)
The problem of limited energy and high household electricity consumption in Indonesia encourages the importance of implementing energy-efficient lighting technology. The still high use of energy-wasting incandescent lamps indicates the low energy literacy of the community in choosing efficient types of lamps. This study aims to analyze and compare the energy efficiency of three generations of lamp technology, namely incandescent lamps, compact fluorescent lamps (CFLs), and LED lamps, with an experimental approach. Testing was carried out using a wattmeter, lux meter, and infrared thermometer in a closed room with controlled conditions. Each type of lamp was tested with a light output equivalent to ±800 lumens. The test results showed that LED lamps had the lowest power consumption of 10 watts with the highest efficiency of 80 lumens per watt and a surface temperature of 45°C. CFLs have a power consumption of 15 watts with an efficiency of 53.3 lumens per watt and a temperature of 70°C. Meanwhile, incandescent lamps consume 60 watts with an efficiency of only 13.3 lumens per watt and a surface temperature of 120°C. Simulation of household use shows that the use of LEDs can save electricity costs of up to 112,500 rupiah per month compared to incandescent lamps. The results of this study provide empirical evidence that LEDs are the most efficient lighting solution in terms of energy, cost, and safety of use for the household sector.